2013
DOI: 10.1111/j.1442-200x.2012.03744.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals in the meconium on preterm mortality: Preliminary study

Abstract: Meconium lead level and gestational age are associated with increased mortality risk in preterm neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In this study, the profiling of detected heavy metal residues in meconium suggested that the participants might commonly expose to these metals (Table 2). Compared to other reports, the extent of exposure may be area specific (Table 4), e.g., Pb, Hg and Cd exposure in inhabitants from heavily contaminated regions and/or industrialized metropolis [34-36] is noticeably higher than those from remote and/or rural areas [14,37,38]. Selected metals detected in our studied subjects may have similar sources, which could be mainly related to contaminated dietary items [39-41] and dust ingestion [42], as a consequence of rapid industrialization and increasing environmental pollution throughout China.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, the profiling of detected heavy metal residues in meconium suggested that the participants might commonly expose to these metals (Table 2). Compared to other reports, the extent of exposure may be area specific (Table 4), e.g., Pb, Hg and Cd exposure in inhabitants from heavily contaminated regions and/or industrialized metropolis [34-36] is noticeably higher than those from remote and/or rural areas [14,37,38]. Selected metals detected in our studied subjects may have similar sources, which could be mainly related to contaminated dietary items [39-41] and dust ingestion [42], as a consequence of rapid industrialization and increasing environmental pollution throughout China.…”
Section: Discussionmentioning
confidence: 83%
“…The reason is that the concentrations of toxic metals and trace elements in a newborn's blood mostly depend on the instantaneous status of circulation and metabolism. 27,28 Meconium is the dark viscous stool that is passed by newborns in the first few days of life. This material may provide an index of mineral accumulation by the fetus, as stool is normally not excreted during intrauterine life.…”
Section: Cadmium Iron Zinc Coppermentioning
confidence: 99%
“…However, the potential of remote sensing in conjunction with GIS largely remains largely underutilized in local mortality surveillance. Few studies incorporating geospatial tools to evaluate all the causes of death of a study area have been reported [ 27 , 28 ]. In our current study, we investigated the land use changes of Suxian District from 1985 to 2012, and explored the association between the disease mortality risk and distance to the Suxian District mining industries area.…”
Section: Introductionmentioning
confidence: 99%